Modified Look-Up Table for Enhancement of Torque Response in Direct Torque Controlled Induction Machine - Goh Wee Yen; Nik Rumzi Nik Idris; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
Basically, the direct torque control (DTC) drive system is operated at light load. At light load, supplying the drive system with rated flux will decrease the efficiency of the system. To maximize the efficiency of drive system, an optimal flux has been applied during steady-state but when a torque is suddenly needed, for example during acceleration, the dynamic of the torque response would be degraded. Therefore, a modification to the voltage vector as well as look-up table has been proposed for the torque response improvement. The proposed voltage vector is generated by adding two adjacent conventional voltage vectors and implemented by using duty ratio. The duty ratio is used to estimate the activation time of each conventional voltage vector in order to produce the proposed voltage vector.